Acceptability and feasibility of policy implementation strategies for taxes earmarked for behavioral health services - Purtle, Jonathan; Stadnick, Nicole A.; Wynecoop, Megan; Walker, Sarah C.; Bruns, Eric J.; Aarons, Gregory A. (Frontiers in Health Services, 2024)
Background: This study's aims are to: 1) Compare the acceptability and feasibility of five types of implementation strategies that could be deployed to increase the reach of evidence-based practices (EBPs) with revenue from policies that earmark taxes for behavioral health services, and 2) Illustrate how definitions of implementation strategies and measures of acceptability and feasibility can be used in policy-focused implementation science research.Web-based surveys of public agency and community organization professionals involved with earmarked tax policy implementation were completed in 2022-2023 (N=211, response rate= 24.9%). Respondents rated the acceptability and feasibility of five types of implementation strategies (dissemination, implementation process, integration, capacitybuilding, and scale-up). Aggregate acceptability and feasibility scores were calculated for each type of strategy (scoring range 4-20). Analyses of variance compared scores across strategies and between organizational actor types.Findings: For acceptability, capacity-building strategies had the highest rating (M=16.3, SD=3.0), significantly higher than each of the four other strategies, p≤. 004), and scale-up strategies had the lowest rating (M=15.6). For feasibility, dissemination strategies had the highest rating (M=15.3, significantly higher than three of the other strategies, p≤ .002) and scaleup strategies had the lowest rating (M= 14.4).Conclusions: Capacity-building and dissemination strategies may be well-received and readily deployed by policy implementers to support EBPs implementation with revenue from taxes earmarked for behavioral health services. Adapting definitions of implementation strategies for policy-focused topics, and applying established measures of acceptability and feasibility to these